2016
DOI: 10.1097/aln.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

In VivoMonitoring of Sevoflurane-induced Adverse Effects in Neonatal Nonhuman Primates Using Small-animal Positron Emission Tomography

Abstract: Background Animals exposed to sevoflurane during development sustain neuronal cell death in their developing brains. In vivo micro-positron emission tomography (PET)/computed tomography imaging has been utilized as a minimally invasive method to detect anesthetic-induced neuronal adverse effects in animal studies. Methods Neonatal rhesus monkeys (postnatal day 5 or 6, 3 to 6 per group) were exposed for 8 h to 2.5% sevoflurane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 96 publications
1
50
0
Order By: Relevance
“…Several studies have also reported that L-carnitine, and particularly ALCAR can protect the developing brain from deleterious effects of exposure to clinically used anesthetic agents [154157]. Treatment with ALCAR protected from neuroinflammation and apoptosis resulting from anesthesia [154157]. It is particularly important that some of these studies used newborn or very young nonhuman primates [154, 155, 157].…”
Section: Neuroprotection By Acetyl-l-carnitine (Alcar)mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also reported that L-carnitine, and particularly ALCAR can protect the developing brain from deleterious effects of exposure to clinically used anesthetic agents [154157]. Treatment with ALCAR protected from neuroinflammation and apoptosis resulting from anesthesia [154157]. It is particularly important that some of these studies used newborn or very young nonhuman primates [154, 155, 157].…”
Section: Neuroprotection By Acetyl-l-carnitine (Alcar)mentioning
confidence: 99%
“…Treatment with ALCAR protected from neuroinflammation and apoptosis resulting from anesthesia [154157]. It is particularly important that some of these studies used newborn or very young nonhuman primates [154, 155, 157]. …”
Section: Neuroprotection By Acetyl-l-carnitine (Alcar)mentioning
confidence: 99%
“…The observed sevoflurane-induced developmental neurotoxicity has yet to be associated with subsequent functional effects in the nonhuman primate as it has with other species [33] but studies looking into this phenomenon are underway [34]. The sevoflurane-induced developmental neurotoxicity that has been demonstrated in previous animal studies [33,35] and in the present work should lead to increased vigilance regarding its use in patients of an age most likely to be susceptible to the adverse effects of general anesthetics [36].…”
Section: Discussionmentioning
confidence: 78%
“…MicroPET/CT is a minimally invasive molecular imaging multimodality that was broadly used in both preclinical and clinical research [34]. These data, plus data from studies by others [56], indicate that dopamine receptors do not mediate the immobility or altered MAC produced by inhaled anesthetics, including sevofl urane, and that D2/D3 receptors in striatum have no contribution to sevofl urane-induced behavioral disturbance and sevofl uraneinduced neurotoxicity [14,54].…”
Section: Discussionmentioning
confidence: 99%
“…There are substantial data indicating that prolonged exposure to sevofl urane can induce neurotoxicity in both rodents and nonhuman primates developing brains [13,14]. Signifi cant behavioral research has also shown that exposure of neonatal mammalian animals to sevofl urane for a long period and/or multiple times will impair performance in the Morris water maze (MWM), a novel-object recognition test (NOR), social behaviors, fear conditioning and recognition memory at all ages [15][16][17].…”
Section: Introductionmentioning
confidence: 99%